The Role Of Immigration In Prevention And Supervision To Combat Human Trafficking Crimes In Indonesia - Racheline Angel Monica; Boedi Prasetyo (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
Human Trafficking (TPPO) is one of the transnational crimes that continues to develop in Indonesia. This crime not only involves the exploitation of victims but also violations of state sovereignty. Immigration plays a strategic role in the prevention and supervision of human trafficking through travel document control, monitoring of border crossings at entry points, and collaboration with other agencies. This article aims to analyze the role of immigration in combating human trafficking in Indonesia, identify challenges faced, and provide recommendations to improve its effectiveness. Using a normative-empirical approach, this research shows that optimization of immigration supervision, utilization of technology, and enhancement of inter-agency cooperation are key to success in efforts to eradicate human trafficking.